Miss Lina's ballerinas and the prince - Davenier, Christine 1961- (Feiwel and Friends, 2011)
In this sequel to "Miss Lina's ballerinas," the girls in the dance class have to go to the zoo to retrieve a somewhat reluctant boy who will dance in the show with them